The Experience of Target Training for the Defense Industry - A. I. Serdyuk; I. D. Belonovskaya; A. B. Radygin (Высшее образование в России)
The paper highlights the changes in the requirements for training of engineering personnel in connection with the rapid development of new machine-building technologies. Along with traditional engineering knowledge and skills, this training should provide the development of students’ competencies in the field of computer technology for design automation, production preparation. It is noted that the rich practical experience of engineers and teachers of the older generation in new conditions becomes obsolete; they can hardly acquire the rapidly changing computer systems of scientific research of subject areas, new technologies, such as 3D graphics and engineering analysis of structures, the system digitalization of production technologies as a whole. To train specialists of a new generation, technical universities should provide: modern educational and laboratory facilities including various computer and controller systems; applicants who have sufficient basic background and technical aptitude; high-skilled teaching staff specialized in modern computer technology willing to upgrade their teaching skills and personal qualifications. The paper dwells on the state support measures for universities to improve personnel training for high-tech industries, which include as a priority the system of personnel training for the military-industrial complex. The authors present an accumulated experience of the Aerospace Institute of the Orenburg State University in the area of stage-by-stage construction of modern educational and laboratory facilities, the formation of student contingent, retraining and raising qualification of the teaching staff, interaction with employers and partners.